Current issues facing the introduction of human papillomavirus vaccine in China and future prospects - Wong, Li Ping; Han, Liyuan; Li, Hui; Zhao, Jinshun; Zhao, Qinjian; Zimet, Gregory D. (Taylor & Francis, 2019)
The introduction of human papillomavirus (HPV) vaccination in China aims to prevent HPV infection in all women. The issues that China might face include high cost of vaccines made in other countries, shortage in HPV vaccine supply, negative events attributed to vaccination (whether justified or not) that jeopardizes the general public’s confidence in the HPV vaccine, cultural and literacy barriers, and sensitivity to receiving a vaccine for a sexually transmitted disease. Ensuring the effective delivery of the HPV vaccine in China, a country with vast economic, geographical, and cultural complexities, will require a commitment of significant resources. In light of the high price of imported vaccines, the availability of locally manufactured HPV vaccines would greatly facilitate the national HPV vaccination program. New evidence supporting the efficacy of a two-dose regime in younger adolescents would also be advantageous in terms of affordability and logistical simplicity of vaccine administration. Furthermore, it would potentially enhance the compliance and uptake, especially for hard to reach women in remote regions. © 2019, © 2019 Taylor & Francis Group, LLC.